Balancing trust and power: a qualitative study of GPs perceptions and strategies for retaining patients in preventive health checks - Marie Broholm-Jørgensen; Ann Dorrit Guassora; Susanne Reventlow; Susanne Oksbjerg Dalton; Tine Tjørnhøj-Thomsen (Taylor & Francis Group, 2017)
Objective: Little is known about how strategies of retaining patients are acted out by general practitioners (GPs) in the clinical encounter. With this study, we apply Grimens' (2009) analytical connection between trust and power to explore how trust and power appear in preventive health checks from the GPs' perspectives, and in what way trust and power affect and/or challenge strategies towards retaining patients without formal education. Design: Data in this study were obtained through semi-structured interviews with GPs participating in an intervention project, as well as observations of clinical encounters. Results: From the empirical data, we identified three dimensions of respect: respect for the patient's autonomy, respect for professional authority and respect as a mutual exchange. A balance of respect influenced trust in the relationship between GP and patients and the transfer of power in the encounter. The GPs articulated that a balance was needed in preventive health checks in order to establish trust and thus retain the patient in the clinic. One way this balance of respect was carried out was with the use of humour. Conclusions: To retain patients without formal education in the clinical encounter, the GPs balanced trust and power executed through three dimensions of respect. In this study, retaining patients was equivalent to maintaining a trusting relationship. A strategic use of the three dimensions of respect was applied to balance trust and power and thus build or maintain a trusting relationship with patients.KEY POINTS   Little is known about how strategies for retaining patients are acted out by GPs in preventive health checks.  •  Retaining patients requires a balance of trust and power, which is executed through three dimensions of respect by the GPs.  •  Challenges of recruiting and retaining patients in public health initiatives might be associated with the balance of respect.